Overview of the Mechanisms of Oxidative Stress: Impact in Inflammation of the Airway Diseases - Giusy Daniela Albano; Rosalia Paola Gagliardo; Angela Marina Montalbano; Mirella Profita (MDPI AG, 2022)
Inflammation of the human lung is mediated in response to different stimuli (e.g., physical, radioactive, infective, pro-allergenic or toxic) such as cigarette smoke and environmental pollutants. They often promote an increase in inflammatory activities in the airways that manifest themselves as chronic diseases (e.g., allergic airway diseases, asthma, chronic bronchitis/chronic obstructive pulmonary disease (COPD) or even lung cancer). Increased levels of oxidative stress (OS) reduce the antioxidant defenses, affect the autophagy/mitophagy processes, and the regulatory mechanisms of cell survival, promoting inflammation in the lung. In fact, OS potentiate the inflammatory activities in the lung, favoring the progression of chronic airway diseases. OS increases the production of reactive oxygen species (ROS), including superoxide anions (O2−), hydroxyl radicals (OH) and hydrogen peroxide (H2O2), by the transformation of oxygen through enzymatic and non-enzymatic reactions. In this manner, OS reduces endogenous antioxidant defenses in both nucleated and non-nucleated cells. The production of ROS in the lung can derive from both exogenous insults (cigarette smoke or environmental pollution) and endogenous sources such as cell injury and/or activated inflammatory and structural cells. In this review, we describe the most relevant knowledge concerning the functional interrelation between the mechanisms of OS and inflammation in airway diseases.